Feasibility of eco-friendly binary and ternary blended binders made of fly-ash and oil-refinery spent catalyst in ready-mixed concrete production - Costa, Carla (2018)
Large-scale recycling of new industrial wastes or by-products in concrete has become a crucial issue for construction materials sustainability, with impact in the three pillars (environmental, social and economic), while still maintaining satisfactory, or improved, concrete performance. The main goal of the paper is to evaluate the technological feasibility of the partial, or total, replacement of fly-ashes (FA), widely used in ready-mixed concrete production, with spent equilibrium catalyst (ECat) from the oil-refinery industry. Three different concrete mixtures with binary binder blends of FA (33.3% by mass, used as reference) and of ECat (16.7% and 33.3%), as well as a concrete mixture with a ternary binder blend with FA and ECat (16.7%, of each) were tested regarding their mechanical properties and durability. Generically, in comparison with commercial concrete (i) 16.7% ECat binary blended concrete revealed improved mechanical strength and durability; (ii): ternary FA-ECat blended binder concrete presented similar properties; and (iii) 33% ECat binary blended concrete has a lower performance. The engineering performance of all ECat concretes meet both the international standards and the reference durability indicators available in the scientific literature. Thus, ECat can be a constant supply for ready-mixed eco-concretes production, promoting synergetic waste recycling across industries.